The role of Wnt signalling in angiogenesis - Olsen, J.; Pohl, Sebastian; Deshmukh, Abhijeet; Visweswaran, Malini; Ward, Natalie; Arfuso, Frank; Agostino, Mark; Dharmarajan, Arunasalam (The Australasian Association of Clinical Biochemists, 2017)
Angiogenesis is a normal biological process wherein new blood vessels form from the growth of pre-existing blood vessels. Preventing angiogenesis in solid tumours by targeting pro-angiogenic factors including vascular endothelial growth factor (VEGF), angiopoietin-1 (Ang-1), basic fibroblast growth factor (bFGF), hepatocyte growth factor, and platelet-derived growth factor (PDGF) is currently under investigation for cancer treatment. Concurrently targeting the cell signalling pathways involved in the transcriptional and post-translational regulation of t hese factors may provide positive therapeutic results. One such pathway is the Wnt signalling pathway. Wnt was first discovered in mice infected with mouse mammary tumour virus, and has been crucial in improving our understanding of oncogenesis and development. In this review, we summarise molecular and cellular aspects of the importance of Wnt signalling to angiogenesis, including ß-catenin-dependent mechanisms of angiogenic promotion, as well as the study of Wnt antagonists, such as the secreted frizzled-related protein family (SFRPs) which have been shown to inhibit angiogenesis. The growing understanding of the underlying complexity of the biochemical pathways mediating angiogenesis is critical to the identification of new molecular targets for therapeutic applications.